Microwave plasma carbonization for the fabrication of polyacrylonitrile-based carbon fiber - Kim, So-Young; Kim, Seong Yun; Lee, Sungho; Jo, Sungmu; Im, Yeon-Ho; Lee, Hun-Su (ELSEVIER SCI LTD, 2015)
Microwave heating is investigated as an alternative method of carbonization process for carbon fiber (CF) in order to reduce the energy costs. In this study, a microwave plasma system is designed for the carbonization process, and stabilized polyacrylonitrile fiber is carbonized using the system. Compared with the CF fabricated by conventional thermal carbonization process, plasma-carbonized CF has higher surface roughness, which can enhance the mechanical interlocking between resin and CF and increase the mechanical properties of the CF Reinforced Polymer (CFRP). Furthermore the mechanical properties of the CF didn't fall behind that of the conventionally carbonized one. As a result, microwave plasma carbonization is a good candidate for the next-generation carbonization processes in the CF industry. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: LOW-TEMPERATURE; RAMAN-SPECTROSCOPY; STABILIZATION; CYCLIZATION; COMPOSITES; CONVERSION; PRECURSORS